Analisis Studi Kelayakan Bisnis pada UMKM: (Studi Kasus Outlet Arfer Kota Palu) - Ayu Kumala Dewi; Maulana Indri; Muhammad Din; Munawarah Munawarah (AKUNTANSI 45, 2025)
This study aims to analyze the business feasibility of Arfer Outlet in Palu City as a form of MSMEs in the beverage sector. The research method uses a qualitative descriptive approach combined with quantitative analysis, focusing on two main aspects, namely the non-financial aspect and the financial aspect. The financial aspect is analyzed through five indicators, namely Net Present Value (NPV), Profitability Index (PI), Payback Period (PP), Internal Rate of Return (IRR), and Average Rate of Return (ARR). The results of the study show that the Arfer Outlet is financially feasible. This is shown by an NPV value of IDR 3,602,691 (positive), PI of 1.35, IRR of 48.93%, and ARR of 85.96%. Although the value of PP of 1.16 years slightly exceeds the economic life of the asset, the difference is still within reasonable limits so the business is still considered feasible. These findings confirm that financial indicators are able to provide an objective picture of business sustainability prospects. Thus, this study not only contributes to the literature on MSME business feasibility studies in the beverage sector, but also provides practical recommendations for the development of micro businesses in Indonesia.